Inhibition of adenovirus replication by CRISPR-Cas9-mediated targeting of the viral E1A gene - Zrinka Didara; Florian Reithofer; Karina Zöttl; Alexander Jürets; Izabella Kiss; Angela Witte; Reinhard Klein (Elsevier, 2023)
DNA-targeting CRISPR-Cas systems are able to cleave dsDNA in mammalian cells. Accordingly, they have been employed to target the genomes of dsDNA viruses, mostly when present in cells in a non-replicative state with low copy numbers. However, the sheer amount of viral DNA produced within a very short time by certain lytically replicating viruses potentially brings the capacities of CRISPR-Cas systems to their limits. The accessibility of viral DNA replication sites, short time of accessibility of the DNA before encapsidation, or its complexation with shielding proteins are further potential hurdles. Adenoviruses are fast-replicating dsDNA viruses for which no approved antiviral therapy currently exists. We evaluated the potency of CRISPR-Cas9 in inhibiting the replication of human adenovirus 5 in vitro by targeting its master regulator E1A with a set of guide RNAs and observed a decrease in infectious virus particles by up to three orders of magnitude. Target DNA cleavage also negatively impacted the amount of viral DNA accumulated during the infection cycle. This outcome was mainly caused by specific deletions, inversions, and duplications occurring between target sites, which abolished most E1A functions in most cases. Additionally, we compared two strategies for multiplex gRNA expression and obtained comparable results.